2018
DOI: 10.1093/jac/dky001
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Streptococcus pneumoniae colonizing children before and after universal use of pneumococcal conjugate vaccines in Brazil: emergence and expansion of the MDR serotype 6C-CC386 lineage

Abstract: Although PNSP strains were polyclonal, most resistant isolates belonged to a single genotype from each period. Higher erythromycin resistance prevalence (42%) in the post-PCV10/13 period was mainly attributed to MDR serotype 6C-CC386. Ongoing surveillance of pneumococcal clonal composition is important to evaluate PCV use outcomes and to identify factors other than PCVs that drive pneumococcal drug resistance evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Indeed, usage of PCV7 and PCV13 in Brazil is very low due to their high cost (Brazil Ministry of Health, 2006; Medeiros et al, 2017; Neves et al, 2017). On the other hand, according to previous studies conducted in Brazil (dos Santos et al, 2013; Medeiros et al, 2017; Neves et al, 2018), our results suggest an important impact on serotype replacement after the implementation of PCV10. PCV10 serotypes showed a decreasing trend over time, especially in the late study period (2011–2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, usage of PCV7 and PCV13 in Brazil is very low due to their high cost (Brazil Ministry of Health, 2006; Medeiros et al, 2017; Neves et al, 2017). On the other hand, according to previous studies conducted in Brazil (dos Santos et al, 2013; Medeiros et al, 2017; Neves et al, 2018), our results suggest an important impact on serotype replacement after the implementation of PCV10. PCV10 serotypes showed a decreasing trend over time, especially in the late study period (2011–2014).…”
Section: Discussionsupporting
confidence: 77%
“…Although emergence of this serotype after PCV7 introduction in certain high-income countries is a well-established fact (Isaacman et al, 2010; Isturiz et al, 2017), serotype 19A emergence after PCV10 introduction in Brazil still seems to be a contradictory issue. While certain studies reveal that occurrence of this serotype has not significantly changed (Medeiros et al, 2017; Neves et al, 2018), others report an increasing rate (Cassiolato et al, 2018; Christophe et al, 2018). We also observed that serotypes 3, 8, 20, and 23A emerged among isolates from IPD cases, whereas serotypes 6C, 35B, and NT isolates were more commonly associated with asymptomatic carriage.…”
Section: Discussionmentioning
confidence: 97%
“…Multi-drug resistant (MDR) isolates were defined as those that were non-susceptible (intermediate or resistant) to at least one drug from three or more different classes of antimicrobial agents, including the beta-lactams (the penicillins benzylpenicillin and ampicillin and the cephalosporin ceftriaxone) [ 29 ]. Apart from the beta-lactams, all drugs tested belong to different classes, namely fluoroquinolones (norfloxacin), lincosamides (clindamycin), macrolides (erythromycin), folate pathway inhibitors (trimethoprim-sulphamethoxazole) and tetracyclines (tetracycline) [ 29 ]. The isolates were frozen (− 20 °C) in STGG storage medium [ 30 ] before being transported to Gothenburg, Sweden, for further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…NOR-resistant isolates were examined by Etest for their susceptibility to ciprofloxacin (CIP), NOR, moxifloxacin (MXF) and levofloxacin (LVX), using breakpoints from the Swedish Reference Group for Antibiotics (SRGA) [23][24][25]. Multidrug-resistance (MDR) was defined as resistance to three or more antimicrobial classes [26].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%